'The burqa is not us (wir sind nicht burka)': strategic Islamophobia and the mainstreaming of nativist appeals. Issue 1 (2nd January 2020) - Druxes, Helga
ABSTRACT: I illuminate the affective and economic factors that drive anti-Muslim sentiment. By lowering the bar of what is sayable, the German New Right creates more acceptance of Islamophobia. Conservative-voting states have held more negative views of Muslims, with the South of Germany being more wary than the North. However, local factors like economic insecurity in de-industrialized regions and high incidence of far-right activities further determine how Germans feel about Islam. Scapegoating Muslims mainstreams 'group-focused enmity' and legitimates violence against minorities and socially weak groups. Currently, populist and far right groups like Pegida and the Alternative for Germany have revived a critique of global economic processes as benefitting only social elites: they dismiss all print journalism as a pack of lies, take a virulent anti-government stance, and create a backlash against career politicians and experts. The fear of refugees gaining access to economic support has provided a convenient scapegoat for processes of devolution.